Does the Pandemic Drive the Use of Artificial Intelligence? Evidence of China - Anton Andreevich KAZANTSEV; Natalia Anatolyevna NAVROTSKAIA (Communications of International Proceedings, 2020)
Artificial intelligence (AI) has become an important component of the digital economy due to the increase in the efficiency of digital systems and the expansion of their scope. The analysis showed that the pandemic really acted as a driver for the introduction of AI into technological, production and economic processes and has already led to irreversible processes of digital transformation of the economy. In the context of the COVID-19 pandemic, the importance of AI has clearly increased; it has shown itself to be unusually effective in solving emergency problems and outlined promising areas for the development of technologies in the coming years. Using the case method, significant changes in technological and economic processes in China were analyzed. The areas of application of artificial intelligence technologies were identified, in which, due to the pandemic, the use of AI was the fastest: 1) providing remote work for business (2) tracking systems, (3) smart city technologies, (4) big data, (5) medicine and (6) unmanned vehicles. The main directions of state support for the development of AI in China are considered.
Keywords: Artificial Intelligence; COVID-19 pandemic; China; technological and economic processes